Digital platformisation dependence-interdependence dynamics in BRICS: from challenges to opportunities in a multipolar world - Polita, Éberson (Revista de Geopolítica, 2025)
In light of world-systems theory hierarchisation and the weaponisation of interdependence for geopolitical purposes, this article aims to provide a systematic assessment on BRICS’ platformisation dynamics on a dependence-interdependence basis with the capitalistic digital core. As an inductive study, it works under the premise that deglobalisation and multipolarity are strategies deployed by the US-led Western collective and the BRICS bloc, respectively. It argues China and Russia are mostly independent from US digital infrastructure, but Brazil, India and South Africa (BIS) are fully dependent. It concludes that, amidst challenges and contradictions, there are ample digital opportunities for the bloc, or parts of it such as the BIS, should they pursue greater cooperation.